Walking as an Alternative to Indonesia’s Oil Consumption Problem - Wahyudi, Heru; Lestasi, Winda Rika; Septiyanti, Ratna; Palupi, Widia Anggi (International Journal of Energy Economics and Policy, 2023)
Oil is one of the vital energy sources in a country. Indonesia is one of the countries that was once the world's primary leading producer but is currently threatened with an oil deficit. This condition certainly requires the right strategy and policy so that Indonesia can meet its domestic oil needs. This study aims to forecast Indonesia's oil consumption and production for 2022-2026 using past data from 1980-2021. This study used the Auto-Regressive Integrated Moving Average (ARIMA) model, where several alternative models were produced in forecasting oil consumption, namely ARIMA (2, 1, 2), (2, 1, 16), (15, 1, 2), and (15, 1, 16) and also alternative models of oil production, namely ARIMA (3, 1, 9), (3, 1, 11), (13, 1, 9), and (13, 1, 11). Based on several alternative models, the best models for forecasting oil consumption and oil production are (2, 1, 16) and (3, 1, 9), respectively. From the results of this study, it is reduced that Indonesia's oil consumption is far above oil production. This, if left unchecked, can negatively affect the country's economy. Thus, research can be used as a reference for policy-making related to fulfilling oil consumption and increasing oil production in Indonesia.